Trade Unionism in Central Europe - TUC Survey, 1946 (pg. 5) (1946)
1946 1945-1960 "Trade Unionism in Central Europe - TUC Survey, 1946 (pg. 5)" [hfr0123_06.jpg], 1946 In November - December 1945, a TUC delegation visited Germany, Czechoslovakia, Austria and Italy to report and advise on the re-establishment of free trade unions.